2023
DOI: 10.1017/s0031182023000793
|View full text |Cite
|
Sign up to set email alerts
|

Impact of endosymbionts on tick physiology and fitness

Agatha O. Kolo,
Rahul Raghavan

Abstract: Ticks transmit pathogens and harbour non-pathogenic, vertically transmitted intracellular bacteria termed endosymbionts. Almost all ticks studied to date contain 1 or more of Coxiella, Francisella, Rickettsia or Candidatus Midichloria mitochondrii endosymbionts, indicative of their importance to tick physiology. Genomic and experimental data suggest that endosymbionts promote tick development and reproductive success. Here, we review the limited information currently available on the potential roles endosymbio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 103 publications
0
2
0
Order By: Relevance
“…In insects, these endosymbionts directly reduce viral replication for dengue and West Nile viruses and act as a manipulator of host reproduction [72,73]. Although little is known about the effects that these bacteria may cause in ticks, they have already been reported to infect at least three tick species, namely: I. ricinus, Rhipicephalus microplus and A. americanum [74][75][76]. Furthermore, a previous study identified that both Wolbachia sequences (wsp and ftsZ genes) were identical to those already reported, such as that associated with an endoparasitoid wasp named Ixodiphagus hookeri.…”
Section: Discussionmentioning
confidence: 99%
“…In insects, these endosymbionts directly reduce viral replication for dengue and West Nile viruses and act as a manipulator of host reproduction [72,73]. Although little is known about the effects that these bacteria may cause in ticks, they have already been reported to infect at least three tick species, namely: I. ricinus, Rhipicephalus microplus and A. americanum [74][75][76]. Furthermore, a previous study identified that both Wolbachia sequences (wsp and ftsZ genes) were identical to those already reported, such as that associated with an endoparasitoid wasp named Ixodiphagus hookeri.…”
Section: Discussionmentioning
confidence: 99%
“…Current information reveals that almost all tick-borne and tick-associated pathogenic bacteria have closely related endosymbiotic relatives coexisting in ticks, as exemplified for Rickettsia , Francisella , Borrelia , and Coxiella [ 4 ]. Additionally, a range of unclassified taxa include members of Anaplasma and Ehrlichia under Anaplasmataceae , and various protozoa under the genera Babesia and Theileria .…”
Section: Pathogens and Endosymbionts—confounding Issuesmentioning
confidence: 99%